Kontribusi Corporate Image Sebagai Pemoderasi Kualitas Layanan Dan Promosi Pada Kepuasan Pengunjung - Sjahruddin Herman; Abdul Kadir (Asosiasi Peneliti Manajemen Adat Indonesia, 2021)
The corporate image moderating contribution is used to explain the relevance of service quality and promotion to visitor satisfaction. An explanatory study based on the realm of positivism is used to prove the response of 170 visitors to the Nipah Mall in Makassar. Analysis of data using WarpPLS 7.0, the results of the study show evidence that the better the quality of service and the more intense the promotion carried out with the support of corporate image is proven to make a significant contribution to visitor satisfaction. On the other hand, the low quality of service is not able to provide a real meaning in increasing satisfaction, even though the management is aggressively promoting, this condition remains the same. This condition is due to the high sense of concern of the nipah mall management to visitors accompanied by high social responsibility so as to create positive value.